(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article discusses the process of stamping by extrusion of hollow metal products. Formulas for the production of hollow products from hard-to-form metals are determined. The article shows the schemes of stress states and the main technological parameters during reverse extrusion.